2017
DOI: 10.1002/elps.201600468
|View full text |Cite
|
Sign up to set email alerts
|

Computational contribution to the electrophoretic enantiomer separation mechanism and migration order using modified β‐cyclodextrins

Abstract: Capillary electrophoresis (CE) is an extremely effective technique in many kinds of separations, including separation of enantiomers. Some additional techniques may be necessary to determine the enantiomer migration order (EMO) and also the mechanism involved in chiral recognition. This paper reports the development and optimization of a CE method for enantioseparation of racemic mixture of both R- and S-stereoisomers of tramadol (TRM) with a computational contribution for the EMO determination and the respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…β-CD derivatives, i.e., neutral (hydroxyethyl-, hydroxypropyl- and methyl-) and anionic (carboxymethyl-, and sulphated-) [21,22,23,24,25,26,27,28,29,30,31,32,33] derivatives were the most commonly used CSs reported. Other commercially-available modified CDs or laboratory-prepared modified CDs with known synthesis were reported.…”
Section: Macromoleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…β-CD derivatives, i.e., neutral (hydroxyethyl-, hydroxypropyl- and methyl-) and anionic (carboxymethyl-, and sulphated-) [21,22,23,24,25,26,27,28,29,30,31,32,33] derivatives were the most commonly used CSs reported. Other commercially-available modified CDs or laboratory-prepared modified CDs with known synthesis were reported.…”
Section: Macromoleculesmentioning
confidence: 99%
“…There were two studies that compared anionic and neutral β-CD derivatives, and both studies concluded that the anionic derivatives provided better selectivity for the analytes tested (cationic higenamine [26] and neutral tramadol [22]). The host-guest interaction with anionic β-CDs are driven by electrostatic interactions, hydrophobic inclusion and hydrogen bonding, which is the case with higenamine.…”
Section: Macromoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that enantiorecognition depends on the formation of association complexes between the anionic β-CD and certain functional groups of tramadol. 31 Tramadol along with other four basic analytes (amlodipine, hydroxyzine, fluoxetine, tolterodine) was used as model compound for the assessment of sulphated maltodextrin potential as chiral selector in CE. Using a 50 mM phosphate BGE at pH 3.0 and 2% (w/v) sulphated maltodextrin as chiral selector baseline enantioseparation December 2019, 25(4), 278-286 | 283 was achieved for all studied analytes.…”
Section: Chiral Determination Of Tramadol Enantiomers By Capillary Elmentioning
confidence: 99%
“…CE has proved to be one of the most effective methods for enantiomers' separation due to its high efficiency, robustness, low cost, simplicity, and diversity regarding different modes, such as ACE , MEKC , and NACE . The enantioseparation can be achieved using different types of chiral selectors, such as cyclodextrin and its derivatives , cyclofructans , crown ether , DNA , macrocyclic antibiotics , ionic liquids , chiral metal‐ion complexes , and proteins . However, when using selectors with UV absorbances, such as proteins and DNA, or when the separation is combined with mass spectrometric detection, the bad effects of selectors on detection must be considered.…”
Section: Introductionmentioning
confidence: 99%